TIMP1 derived from pancreatic cancer cells stimulates Schwann cells and promotes the occurrence of perineural invasion. (10th October 2022) - Tian, Zhenfeng; Ou, Guangsheng; Su, Mingxin; Li, Ruomeng; Pan, Lele; Lin, Xingyi; Zou, Jinmao; Chen, Shangxiang; Li, Yaqing; Huang, Kaihong; Chen, Yinting
Abstract: Perineural invasion (PNI) occurs in most pancreatic ductal adenocarcinomas (PDACs). The relationship between cancer cells and peripheral nerves, however, is unknown. Therefore, we focused on the cooperation of PDAC cells and peripheral nerve astrocytes, Schwann cells (SCs), in PNI. The mutual tumor-supportive secretory cytokines between SCs (sNF96.2) and PDAC cells (PANC-1, BxPC-3) were screened by human cytokine arrays and verified. The prognostic value of selected cytokines and SC-associated markers was confirmed in PDAC patients. TIMP1 and CCL7 were found to form a paracrine feedback loop between PDAC cells and SCs. PDAC cell-derived TIMP1 promotes SCs proliferation and migration via CD63/PI3K/AKT signaling. CCL7 secreted from SCs enhances PDAC cell migration, invasion and expression of TIMP1 via CCR2/STAT3. PDAC cell-SC cooperation in PNI was blocked when TIMP1 knockdown in vitro and in vivo. Finally, TIMP1, CCL7 and SC-associated markers were correlated with PNI and prognosis in PDAC patients. In conclusion, SCs collaborate with PDAC cells through the TIMP1-CCL7 paracrine feedback loop to promote PNI. TIMP1 knockdown in PDAC cells suppresses PNI. Strategies to disrupt the TIMP1-CCL7 feedback loop might be developed to inhibit PNI in PDAC. Highlights: A TIMP1-CCL7 positive feedback loop exists between Schwann cells (SCs) and PDAC cells. TIMP1 derived from PDAC cells activates SCs via the CD63/PI3K/AKT axis and promotes PNI of PDAC. CCL7 secreted by SCs enhances TIMP1 expression and PDAC progression by the CCR2/STAT3 pathway.